PENGEMBANGAN KEMAMPUAN MOTORIK ANAK USIA DINI MELALUI EKSPLORASI INOVATIF ALAT PERMAINAN SEDERHANA DI POS PAUD TERPADU KALIJUDAN - Enoch David Lontolawa; Intan Ramadhita Pramidanirwa; Laisya Kezia Clarinta (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Motor skill development in early childhood plays a crucial role in supporting physical, cognitive, social, and emotional growth. Efforts to enhance motor skills can be achieved through the use of simple play materials and an integrated approach. At Pos PAUD Terpadu Kalijudan, this effort is implemented through the application of innovative play materials designed to stimulate various aspects of motor skill development. The integrated approach at PAUD Kalijudan involves incorporating these play materials into the daily curriculum, thereby creating an environment that encourages children to practice motor skills in a fun and practical context. The program also includes training for educators and parents to ensure the effective and consistent use of these play materials both at home and in school. The implementation methodology includes phases such as Observation and Evaluation, Determination of Motor Skill Practice Types and Creation of Play Media, Socialization, and Practical Application. Through this approach, it is anticipated that children will be able to explore their motor skills, thereby supporting their overall physical, cognitive, social, and emotional development